2017
DOI: 10.1016/j.surg.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative serum CEA and CA125 levels are supplementary to perioperative CA19-9 levels in predicting operative outcomes of pancreatic ductal adenocarcinoma

Abstract: The postoperative monitoring of CEA and CA125 provided prognostic significance to the measurement of CA19-9 in pancreatic cancer after resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 21 publications
2
49
0
1
Order By: Relevance
“…Preoperative TM, particularly CA19-9, was a strong prognostic factor of the postoperative survival of patients with PC. 10,11 However, based on our aforementioned data, patients with negative TMs still had severe postoperative results, of which 30% had survived after 5 years. Postoperative prognostication using TMs has two significant limitations.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Preoperative TM, particularly CA19-9, was a strong prognostic factor of the postoperative survival of patients with PC. 10,11 However, based on our aforementioned data, patients with negative TMs still had severe postoperative results, of which 30% had survived after 5 years. Postoperative prognostication using TMs has two significant limitations.…”
Section: Discussionmentioning
confidence: 89%
“…Preoperative serum CA19-9 level is positively associated with tumor metastasis, and an elevated CA19-9 level is correlated to early recurrence and death. 10,11 However, serum CA19-9 level alone is not sufficient in predicting postoperative survival because it is usually elevated in case of biliary obstruction. 12 In addition, approximately 5%e10% of the population are Lewis negative individuals, and they are documented to have scarce or no CA19-9 secretion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that CA242 levels were elevated in a variety of digestive system cancers, including pancreatic cancer, gallbladder cancer, cholangiocarcinoma, colorectal cancer, and gastric cancer, which was consistent with previous reports. The AUC values of the ROC curves for pancreatic cancer, gallbladder carcinoma, and cholangiocarcinoma were all greater than 0.8, but only pancreatic cancer has been studied in detail [4,10,13,17,22,[25][26][27]. Previous studies have shown that CA242 alone or in combination with other biomarkers can predict the diagnosis, progression, and prognosis of pancreatic cancer [4, 7, 10, 12-16, 23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, although CA242 has been used as a rst-line clinical marker of pancreatic cancer for more than a decade [11], research on it has continued. CA242 is not merely a diagnostic predictor [12,13] but also participates in forecasting the progression and prognosis of many tumors [14][15][16]. In pancreatic cancer, colorectal cancer [17][18][19], gastric cancer [20,21] and other tumors and when used alone or in combination with CA19-9, CA50, CEA and other biomarkers [4,7,14,[22][23][24], CA242 is gradually becoming better understood and applied more broadly.…”
Section: Introductionmentioning
confidence: 99%